British women writing fiction - Werlock, Abby H. P. (Tuscaloosa : University of Alabama Press, 2000)
"British women in the second half of the 20th century have produced a body of work that is as diverse as it is entertaining. This book offers an informal, jargon-free introduction to the fiction of sixteen contemporary writers either brought up or now living in England. Book jacket."--Jacket
Foreword / Regina Barreca -- Acknowledgments -- Introduction / Abby P. Werlock -- Iris Murdoch: mapping the country of desire / Roberta White -- "Transformed and translated": the colonized reader of Doris Lessing's Canopus in Argos space fiction / Susan Rowland -- P.D. James and the dissociation of sensibility / Eric Nelson -- Retrofitting the Raj: Ruth Prawer Jhabvala and the uses and abuses of the past / Judie Newman -- Anita Brookner: on reaching for the sun / Kate Fullbrook -- "Witness to their vanishing": Elain.
Includes bibliographical references and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
English.
Keywords: English fiction -- Women authors -- History and criticism; Women and literature -- Great Britain -- History -- 20th century; English fiction -- 20th century -- History and criticism; English fiction -- History and criticism; English literature -- Women authors -- History and criticism; Roman anglais -- Histoire et critique; Femmes et littérature -- Grande-Bretagne -- Histoire -- 20e siècle.; Roman anglais -- 20e siècle -- Histoire et critique; Écrits de femmes anglais -- Histoire et critique; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh; English literature -- Women authors; English fiction; English fiction -- Women authors; Women and literature; Great Britain; 1900-1999; Criticism, interpretation, etc; History